2016
DOI: 10.21873/anticanres.11104
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutant Status, p16 and β-catenin Expression May Predict Local Recurrence in Patients Who Underwent Transanal Endoscopic Microsurgery (TEMS) for Stage I Rectal Cancer

Abstract: Abstract. Background The method of local excision, that has recently, gained wider acceptance, in early rectal cancer, is transanal endoscopic microsurgery (TEMS). TEMS generally offers advantages in operative access and oncological clearance over transanal resection (TAR), but recently a number of similar logic techniques with various rectal ports for endoscopic excision of rectal tumours has been invented. Those methods are collectively named transanal minimal-invasive surgery (TAMIS) and for oncological pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This seems to support the assumption that early cancer recurrence can represent the reflection of a specific carcinogenesis pathway where KRAS plays an important role, and it is involved at early stages. Similar findings were reported in one of our recently published study (21), where KRAS is linked with local recurrence in Stage I Rectal Cancer following Transanal Endoscopic Microsurgery (TEMS).…”
Section: Discussionsupporting
confidence: 90%
“…This seems to support the assumption that early cancer recurrence can represent the reflection of a specific carcinogenesis pathway where KRAS plays an important role, and it is involved at early stages. Similar findings were reported in one of our recently published study (21), where KRAS is linked with local recurrence in Stage I Rectal Cancer following Transanal Endoscopic Microsurgery (TEMS).…”
Section: Discussionsupporting
confidence: 90%
“…Similar notions have been discussed in the case of CRC, where in the classic adenoma-carcinoma pathway, KRAS mutations seem to appear early in the neoplastic route. Several studies concluded that KRAS may play a significant role in early stage CRC (27)(28)(29). In 1988, Vogelstein et al stated that early mutations of adenomatous polyposis coli gene result in deregulation of the wingless-related integration site (WNT) pathway (30); KRAS mutations follow deregulation of the WNT pathway and certainly take place prior to TP53 gene inactivation.…”
Section: Kras Mutations As Biomarkers Of Early-stage Type I Ecmentioning
confidence: 99%
“…Firstly, in a subgroup of patients with concomitant KRAS mutation and p14 ARF methylation, local recurrences and/or metastases were significantly more often detected (P=0.027). Previous studies have shown that the presence of KRAS mutations in the early stages of RC is associated with the occurrence of distant recurrences in the later stages of the disease [22]. Mutation of this gene in LARC is common, but the mutational status of the KRAS gene is not enough to predict more aggressive tumor behavior, and other parameters are needed to indicate a potential risk of recurrence [23].…”
Section: Discussionmentioning
confidence: 99%